2008
DOI: 10.1038/sj.bjc.6604652
|View full text |Cite
|
Sign up to set email alerts
|

Telomere maintenance and dysfunction predict recurrence in paediatric ependymoma

Abstract: We have recently described the enzymatic subunit of telomerase (hTERT) as an important prognostic marker for paediatric ependymoma. Because of the lack of good, representative pre-clinical models for ependymoma, we took advantage of our large cohort of ependymoma patients, some with multiple recurrences, to investigate telomere biology in these tumours. Our cohort consisted of 133 ependymomas from 83 paediatric patients and included 31 patients with recurrences. Clinical outcome was measured as overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
5
28
0
3
Order By: Relevance
“…The results showed that Ab 3 (NCL-L-hTERT antibody) was not absorbed any more with the nucleolin peptide than were the other anti-hTERT antibodies. In agreement with other researchers (27,70,71,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) and despite the objection raised by Wu et al (64) the Ab 3 proved suitable for hTERT detection. Mitsuishi et al (98) not only confirmed the consideration of Wu et al (64), but also found excellent correlation between nucleolin expression and telomerase activity levels in Bowens's disease and in normal sunexposed skin.…”
Section: Comparison Of Htert Results In Basal Cell Carcinomas and Squsupporting
confidence: 76%
See 1 more Smart Citation
“…The results showed that Ab 3 (NCL-L-hTERT antibody) was not absorbed any more with the nucleolin peptide than were the other anti-hTERT antibodies. In agreement with other researchers (27,70,71,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) and despite the objection raised by Wu et al (64) the Ab 3 proved suitable for hTERT detection. Mitsuishi et al (98) not only confirmed the consideration of Wu et al (64), but also found excellent correlation between nucleolin expression and telomerase activity levels in Bowens's disease and in normal sunexposed skin.…”
Section: Comparison Of Htert Results In Basal Cell Carcinomas and Squsupporting
confidence: 76%
“…Mitsuishi et al (98) not only confirmed the consideration of Wu et al (64), but also found excellent correlation between nucleolin expression and telomerase activity levels in Bowens's disease and in normal sunexposed skin. In the immunohistochemical study of Ridley et al (99) hTERT expression in ependymomas with Ab 3 showed very strong correlation with the outcome in pediatric intracranial ependymomas (95). Furthermore, Khurts et al (100) revealed experimentally that nucleolin interacts with telomerase and changes its subcellular localization.…”
Section: Comparison Of Htert Results In Basal Cell Carcinomas and Squmentioning
confidence: 99%
“…Toomey et al (65) explored hTERT expression in patients with an operable lung carcinoma using an anti-hTERT antibody by Santa Cruz (code C20) and found no correlation in the Kaplan-Meier curve between high hTERT expression and patient outcome. Tabori et al (66), using our Ab 3 in ependymomas, were able to demonstrate a significantly shorter survival time in patients with higher hTERT expression (p=0.05). In patients with a mamma carcinoma, hTERT as demonstrated by Elkak et al (67) using the NCL-hTERT antibody (our Ab 3) did not correlate in the ¯2 test with lymph node status, grading or tumor size.…”
Section: Correlation Of Htert Score Values and Telomerase Activity Inmentioning
confidence: 99%
“…Xiao et al (106) conclude from their studies on culture cells and tissues fixated in formalin that chicken IgG antibodies can have definite advantages over the commonly used mammal IgG antibodies and exhibit less non-specific staining. Irrespective of the afore-mentioned objections, many authors continue to use the monoclonal NCL-L-hTERT for immunohistochemical proof of hTERT (63,66,(107)(108)(109)(110)(111)(112).…”
Section: Cells Which May Be Responsible For Telomerase Activity Outsimentioning
confidence: 99%
“…These tumors, specifically gliomas and neuroblastomas, share unique extremes of clinicobiological behavior: spontaneous growth arrest, on the one hand, and relentless progression even with maximal therapy, on the other (2,3). Previous work from our group and others has shown that the lack of telomere maintenance is responsible for growth arrest and predicts the risk of recurrence in pediatric low-grade gliomas (2), ependymomas (4,5), and stage IV-S neuroblastomas (6), suggesting that telomerase inhibition could reverse their malignant phenotype by altering their self-renewal capabilities.…”
Section: Introductionmentioning
confidence: 99%